Memimpin di era perubahan untuk Indonesia dan dunia : belajar kepemimpinan Presiden SBY untuk anak muda Indonesia - Pandjaitan, Hinca I. P. (Hinca Ikara Putra), 1964- (Pasar Minggu, Jakarta : Kubah Ilmu, 2012)
Leadership and policies of Susilo Bambang Yudhoyono, the 6th president of Indonesia; collected articles.
In Indonesian, and some articles in English.
Keywords: Yudhoyono, Susilo Bambang, -- 1949-; Presidents -- Indonesia; Political leadership -- Indonesia